Lead screw and preparation method and application thereof
By forming a multi-layer cermet thread layer on the steel rod base and performing deep cold treatment, the gap in accuracy retention and wear resistance of existing lead screws is solved, and higher hardness and wear resistance are achieved, which is suitable for long-term use in complex environments.
Patent Information
- Application Number
- CN202411930558.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-25
AI Technical Summary
There are gaps in existing high-precision lead screws in terms of accuracy retention and wear resistance, making it difficult to serve for a long time in complex environments.
By setting up a multi-layer cermet layer on the steel rod base material, the threaded part is cermet material, and a thread layer is formed layer by layer by layer by laser cladding technology. Combined with deep cold treatment technology, the hardness and wear resistance of the screw are improved.
It significantly improves the hardness, wear resistance and corrosion resistance of the screw surface, thereby improving its accuracy retention and service life, and can operate stably in complex environments for a long time.
Smart Images

Figure CN119685817A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite metal materials, and in particular to a lead screw and a preparation method and application thereof. Background Art
[0002] High-precision lead screw is one of the core functional components of industrial machine tools, which directly determines the performance, technical level, quality and reliability of industrial machine tools, and is the commanding height that must be conquered in the process of transformation and upgrading of my country's manufacturing industry. Compared with foreign countries, the initial accuracy of my country's highest-level lead screw products can be almost the same as the international advanced level. The main gap is reflected in the wear resistance and fatigue life that determine the accuracy retention and functional reliability, which is related to the basic materials, forming process and other aspects; therefore, the current high-precision retaining lead screw materials and their preparation technology are in urgent need of breakthroughs.
[0003] At present, the metal materials used for screws generally adopt high carbon chromium bearing steel GCr15, medium carbon steel 4150H, etc. After annealing or tempering, the raw materials are tempered by medium frequency and high frequency induction quenching, and finally the screw products are obtained after a series of mechanical processing. The initial accuracy of the screw products processed by the above raw materials and processes can be almost the same as that of foreign products, but there is still a large gap in accuracy retention. Therefore, providing a screw product with wear resistance, high precision and good accuracy retention and its preparation method is of great significance to overcome the technical problem of poor accuracy retention of screw products prepared by the existing technology.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a lead screw, which, by arranging a metal ceramic layer on a steel rod substrate and making the threaded portion of a metal ceramic material, can greatly improve the hardness, wear resistance and corrosion resistance of the lead screw surface, thereby improving its precision retention and allowing it to serve in complex environments.
[0006] The second purpose of the present invention is to provide a method for preparing a lead screw as described above, wherein a metal ceramic thread is formed on a steel rod substrate by layer-by-layer laser cladding, and the shape and size of the thread are controlled by controlling the width and thickness of each layer of the cladding layer. The lead screw obtained has high precision, small deformation increase, good wear resistance, good precision retention, and a long mean time between failures.
[0007] The third object of the present invention is to provide a ball screw pair, comprising the screw as described above or a screw made by the screw preparation method as described above.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] A lead screw comprises a cylindrical steel rod substrate and a metal ceramic layer located on the outer surface of the steel rod substrate. The metal ceramic layer is a multi-layer structure, comprising a ceramic base layer covering the entire circumferential outer surface of the steel rod substrate and a threaded layer located on the ceramic base layer.
[0010] Preferably, the thickness H of the metal ceramic layer and the diameter D of the lead screw satisfy the following relationship: H=(0.08-0.15)D.
[0011] Preferably, the metal ceramic layer comprises, by mass percentage, 10% to 60% WC, 0% to 40% TiC, 0% to 40% SiC, and 20% to 60% iron-based material having the same composition as the steel rod substrate;
[0012] And / or, the steel rod substrate includes any one of 42CrMo steel, GCr15 steel, and 40Cr steel.
[0013] Preferably, the number of layers n of the metal ceramic layer is 4 to 6 layers, wherein the first layer is the ceramic base layer, the second to nth layers constitute the threaded layers, and the thread width of the threaded layers decreases layer by layer starting from the second layer.
[0014] Preferably, in the multilayer structure of the metal ceramic layer, the thread width of the second layer is 0.85 to 0.95 times the pitch of the lead screw; and / or the thickness of any layer is 0.01 to 0.04 times the diameter of the lead screw.
[0015] A method for preparing a lead screw according to any one of the aforementioned embodiments comprises the following steps:
[0016] The steel rod substrate is heat treated, and metal ceramic powder is clad on the outer peripheral surface of the steel rod substrate in multiple layers by laser cladding to form a metal ceramic layer, which is then cryogenically treated and ground to obtain a metal ceramic layer;
[0017] The cladding step includes cladding a cladding layer on the entire outer circumference of the steel rod substrate to form a ceramic base layer, then cladding along a spiral line on the ceramic base layer to obtain a spiral second cladding layer, and continuing to clad along the spiral line on the second cladding layer, and repeating this process until a thread layer of desired thickness is obtained.
[0018] Preferably, in terms of mass percentage, the metal ceramic powder includes 10% to 60% WC, 0% to 40% TiC, 0% to 40% SiC, and 20% to 60% iron-based powder having the same composition as the steel rod substrate.
[0019] Preferably, the laser power of the laser cladding is 1000-5000W.
[0020] Preferably, the powder feeding rate of the laser cladding is 10-50 g / min.
[0021] Preferably, the spot size of the laser cladding is 2-6 mm.
[0022] Preferably, the moving linear speed of the laser cladding is 5 to 50 mm / s, and the overlap rate is 5% to 80%.
[0023] Preferably, in the cladding process, an inert gas is used to protect the cladding parts, and the flow rate of the inert gas is 10 to 50 L / min.
[0024] Preferably, the number of layers of the laser cladding is 4 to 6 layers.
[0025] Preferably, the temperature of the cryogenic treatment is -80°C to -120°C, and the time of the cryogenic treatment is 1 to 5 hours.
[0026] A ball screw pair comprises a screw as described in any one of the aforementioned embodiments or a screw produced by the method for producing a screw as described in any one of the aforementioned embodiments.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention clads a metal ceramic material with high temperature resistance, corrosion resistance, good chemical stability, high hardness, high strength and good wear resistance on a steel rod substrate to form a composite metal material with a gradient structure. The thread layer and the bottom of the groove between the threads are both composed of metal ceramic materials, which can significantly improve the hardness, wear resistance and corrosion resistance of the screw surface, thereby improving the accuracy retention of the screw and can serve in complex environments. The screw prepared by laser cladding composite cryogenic treatment technology has high precision, high accuracy retention, good stability, not easy to deform, long service life, and can reduce the risk of failure. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 A cross-sectional view of a lead screw before grinding provided by an embodiment of the present invention;
[0031] Figure 2 For the present invention Figure 1 A partial enlarged view of
[0032] Figure 3A partial enlarged view of the lead screw after grinding provided in an embodiment of the present invention.
[0033] Reference numerals:
[0034] 1-steel rod substrate; 2-metal ceramic layer; 21-ceramic base layer; 22-thread layer. DETAILED DESCRIPTION
[0035] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0036] like Figure 1 and Figure 2 As shown, the first aspect of the present invention provides a lead screw, comprising a cylindrical steel rod substrate 1 and a metal ceramic layer 2 located on the outer surface of the steel rod substrate 1, the metal ceramic layer 2 is a multi-layer structure, including a ceramic base layer 21 coated on the entire circumferential outer surface of the steel rod substrate 1 and a threaded layer 22 located on the ceramic base layer 21, and the cross-sectional structure of the threaded layer 22 along the axial cross-section of the steel rod substrate (the cross-section passing through the center line of the steel rod substrate) is a trapezoidal structure with arc-shaped sides (such as Figure 3 shown).
[0037] Ceramic materials have many excellent properties, such as high temperature resistance, corrosion resistance, good chemical stability, high hardness, high strength, good wear resistance, etc., so they can be used to manufacture products and parts that serve in harsh environmental conditions such as high temperature, corrosion, wear resistance, tension and compression. Metal ceramic materials are clad on steel rod substrates to form composite metal materials with gradient structures, which can improve the hardness, corrosion resistance and wear resistance of the material surface. The screw provided by the present invention has a thread layer and the bottom of the groove between the threads made of metal ceramic materials, which can significantly improve the hardness, wear resistance and corrosion resistance of the screw surface, thereby improving the accuracy retention of the screw and allowing it to serve in complex environments.
[0038] If the threaded layer of metal ceramic material is directly arranged on the steel rod substrate, due to the small contact area between the two and the fact that they are heterogeneous materials, the bonding between the threaded layer and the steel rod substrate is poor, and the steel rod substrate will be seriously deformed. To address this problem, the present invention increases the contact area between the metal ceramic layer and the steel rod substrate by arranging a fully covered ceramic base layer on the entire outer circumference of the steel rod substrate, improves the bonding force between the metal ceramic layer and the steel rod substrate, and reduces the deformation of the steel rod substrate. Then, a threaded layer is arranged on the ceramic base layer. The threaded layer and the ceramic base layer are made of the same material and have good bonding. This structural arrangement can improve the bonding force between the threaded layer and the steel rod substrate, avoid the threaded layer from falling off during use under complex working conditions, and further improve the accuracy retention of the lead screw.
[0039] In some specific embodiments of the present invention, the thickness H of the metal ceramic layer and the diameter D of the screw satisfy the following relationship: H = (0.08-0.15) D, that is, the thickness H of the metal ceramic layer is 0.08-0.15 times the diameter D of the screw, for example, it can be any point value among 0.08 times, 0.09 times, 0.10 times, 0.11 times, 0.12 times, 0.13 times, 0.14 times, 0.15 times, or a range value consisting of any two point values. If the thickness of the metal ceramic layer is too small, the wear resistance will be reduced, thereby affecting the service life; if the thickness of the metal ceramic layer is too large, the screw will have insufficient toughness, increased brittleness, and easy fracture risk.
[0040] In some specific embodiments of the present invention, the metal ceramic layer includes, by mass percentage, 10% to 60% WC, 0% to 40% TiC, 0% to 40% SiC, and 20% to 60% iron-based material having the same composition as the steel rod substrate. Adding part of the iron-based material having the same composition as the steel rod substrate to the metal ceramic layer can improve the bonding between the metal ceramic layer and the steel rod substrate, thereby improving the precision retention of the lead screw.
[0041] In some embodiments, typically but not limiting, for example, in the metal ceramic layer, the mass percentage of WC can be any value among 10%, 20%, 30%, 40%, 50%, 60%, or a range consisting of any two values; the mass percentage of TiC can be any value among 0%, 10%, 20%, 30%, 40%, or a range consisting of any two values; the mass percentage of SiC can be any value among 0%, 10%, 20%, 30%, 40%, or a range consisting of any two values; the mass percentage of the iron-based material consistent with the composition of the steel rod substrate can be any value among 20%, 30%, 40%, 50%, 60%, or a range consisting of any two values.
[0042] In some specific embodiments of the present invention, the steel rod substrate used includes any one of 42CrMo steel, GCr15 steel, and 40Cr steel.
[0043] In some specific embodiments of the present invention, the number of layers n of the metal ceramic layer is 4 to 6 layers, for example, it can be 4 layers, 5 layers or 6 layers; wherein the first layer (the cladding layer closest to the steel rod substrate) is the ceramic base layer, the 2nd to nth layers constitute the threaded layer, and the thread width of the threaded layer decreases layer by layer starting from the second layer. Too many layers of metal ceramic layers will result in a single ceramic layer that is too thin and poor bonding between layers; too few layers will result in a single ceramic layer that is too thick and the brittleness of the ceramic layer will increase, and sudden falling of the pieces may occur during use. Therefore, too many or too few layers will result in a decrease in the accuracy retention of the screw, and the number of metal ceramic layers needs to be reasonably controlled.
[0044] In some specific embodiments of the present invention, in the multilayer structure of the metal ceramic layer, the thread width of the second layer is 0.85 to 0.95 times the pitch of the screw, for example, it can be any point value among 0.85 times, 0.87 times, 0.9 times, 0.92 times, 0.95 times, or a range value composed of any two points; and / or, the thickness of any ceramic layer is 0.01 to 0.04 times the diameter of the screw, for example, it can be any point value among 0.01 times, 0.02 times, 0.03 times, 0.04 times, or a range value composed of any two points.
[0045] In some specific embodiments of the present invention, the number of metal ceramic layers is 5 layers, wherein the first layer covers the outer circumference of the entire steel rod substrate and has a thickness of 0.01 to 0.04 times the diameter of the screw, the thread width of the second layer is 0.85 to 0.95 times the pitch of the screw, and the thickness is 0.01 to 0.02 times the diameter of the screw, the thread width of the third layer is 0.7 to 0.9 times the pitch of the screw, and the thickness is 0.01 to 0.03 times the diameter of the screw, the thread width of the fourth layer is 0.5 to 0.8 times the pitch of the screw, and the thickness is 0.01 to 0.03 times the diameter of the screw, and the thread width of the fifth layer is 0.4 to 0.75 times the pitch of the screw, and the thickness is 0.02 to 0.04 times the diameter of the screw.
[0046] A second aspect of the present invention provides a method for preparing a lead screw as described in any one of the aforementioned embodiments, comprising the following steps:
[0047] The steel rod substrate is heat treated, and the metal ceramic powder is clad on the outer peripheral surface of the steel rod substrate in multiple layers by laser cladding to form a metal ceramic layer, which is then cryogenically treated and precisely ground to obtain the metal ceramic layer;
[0048] The cladding step includes cladding a cladding layer on the entire outer circumference of the steel rod substrate to form a ceramic base layer, then cladding along a spiral line on the ceramic base layer to obtain a spiral second cladding layer, and then continuing to clad along the spiral line on the second cladding layer, and repeating this process until a thread layer of desired thickness is obtained. When cladding the thread layer, the width of the cladding layer is reduced layer by layer, so that the cross-sectional structure of the thread layer along the axial cross-sectional direction is a trapezoidal structure with arc-shaped sides after grinding.
[0049] The method of the present invention uses laser cladding to coat metal ceramic powder with high hardness, high corrosion resistance and high wear resistance onto a steel rod substrate. After cladding to form a ceramic base layer, cladding is performed along a spiral line on the ceramic base layer to form a thread, so that the thread layer of the screw and the bottom of the groove between the threads are both made of metal ceramic materials, which can significantly improve the wear resistance of the screw and further improve its accuracy retention. Deep cold treatment after cladding can improve the mechanical properties and adhesion of the cladding layer, which can further improve the accuracy retention and service life of the screw.
[0050] In some specific embodiments of the present invention, the metal ceramic powder used includes WC10% to 60%, TiC 0% to 40%, SiC 0% to 40%, and iron-based powder 20% to 60% having the same composition as the steel rod substrate, by mass percentage. The present invention utilizes metal ceramic materials to increase the wear resistance of the lead screw, and at the same time, iron-based powder having the same composition as the steel rod substrate is added to the metal ceramic powder to improve the bonding force between the metal ceramic material and the steel rod substrate, thereby preventing the metal ceramic layer from falling off during use, and the two can synergistically significantly improve the accuracy retention of the lead screw.
[0051] In some specific embodiments of the present invention, the laser power of laser cladding is 1000-5000W, for example, it can be any point value among 1000W, 1500W, 2000W, 2500W, 3000W, 3500W, 4000W, 4500W, and 5000W, or a range value consisting of any two point values.
[0052] In some specific embodiments of the present invention, the powder feeding rate of laser cladding is 10 to 50 g / min. For example, it can be any point value among 10 g / min, 18 g / min, 25 g / min, 30 g / min, 35 g / min, 40 g / min, 45 g / min, and 50 g / min, or a range value consisting of any two point values.
[0053] The parameter settings of laser cladding power and powder feeding amount are related to the thickness of the cladding layer.
[0054] In some specific embodiments of the present invention, the spot size of laser cladding is 2 to 6 mm, for example, it can be any point value among 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, or a range value consisting of any two point values.
[0055] In some specific embodiments of the present invention, the moving linear speed of laser cladding is 5 to 50 mm / s, for example, it can be any point value among 5 mm / s, 10 mm / s, 15 mm / s, 20 mm / s, 30 mm / s, 40 mm / s, and 50 mm / s, or a range value consisting of any two point values; the overlap rate is 5% to 80%, for example, it can be any point value among 5%, 10%, 20%, 40%, 50%, 60%, and 80%, or a range value consisting of any two point values.
[0056] In some specific embodiments of the present invention, an inert gas is used to protect the cladding part during the cladding process, and the flow rate of the inert gas is 10 to 50 L / min. For example, it can be any point value among 10 L / min, 15 L / min, 20 L / min, 25 L / min, 30 L / min, 40 L / min, and 50 L / min, or a range value consisting of any two point values.
[0057] In some specific embodiments of the present invention, the number of laser cladding layers is 4 to 6 layers, for example, it can be 4 layers, 5 layers or 6 layers. If the number of cladding layers is too many, the bonding property decreases, and if the number of cladding layers is too few, the single layer thickness is too large, and the brittleness of the cladding layer increases.
[0058] In some specific embodiments of the present invention, the number of layers of laser cladding is 5 layers. The specific process is as follows: first, a first cladding layer (ceramic base layer) is clad on the entire outer peripheral surface of the steel rod substrate, and the thickness is 0.01 to 0.04 times the diameter of the screw. The second layer is clad along the spiral line, and the width is 0.85 to 0.95 times the pitch of the screw, and the thickness is 0.01 to 0.02 times the diameter of the screw. The third layer continues to be clad along the spiral line on the second cladding layer. The width is 0.7 to 0.9 times the screw pitch, and the thickness is 0.01 to 0.03 times the screw diameter. The fourth layer continues to be clad along the spiral line on the third layer of cladding, with a width of 0.5 to 0.8 times the screw pitch and a thickness of 0.01 to 0.03 times the screw diameter. The fifth layer continues to be clad along the spiral line on the fourth layer of cladding, with a width of 0.4 to 0.75 times the screw pitch and a thickness of 0.02 to 0.04 times the screw diameter.
[0059] In some specific embodiments of the present invention, the temperature of the cryogenic treatment is -80℃~-120℃, for example, it can be any point value among -80℃, -90℃, -100℃, -110℃, -120℃ or a range value consisting of any two point values; the time of the cryogenic treatment is 1~5h, for example, it can be any point value among 1h, 2h, 3h, 4h, 5h or a range value consisting of any two point values. If the cryogenic temperature is too high, the microstructure transformation temperature is not reached, and the effect is not ideal; if the cryogenic temperature is too low, the thermal shock is large, which is easy to cause the workpiece to crack, and the improvement effect of the mechanical properties is not obvious.
[0060] In some specific embodiments of the present invention, the cryogenic treatment process includes: reducing the temperature of the workpiece to -80°C to -120°C at a cooling rate of 2 to 8°C / min, keeping it warm for 1 to 5 hours, and then slowly raising the temperature to room temperature at a rate of 2 to 10°C.
[0061] In some specific embodiments of the present invention, the ratio of the pitch to the diameter of the lead screw is no greater than 0.5.
[0062] A third aspect of the present invention provides a ball screw pair, comprising a screw as described in any one of the aforementioned embodiments, or a screw produced by the method for producing a screw as described in any one of the aforementioned embodiments.
[0063] The following is a detailed description of some embodiments of the present invention in conjunction with specific examples. The raw materials used in the examples can be purchased from the market unless otherwise specified.
[0064] Example 1
[0065] This embodiment takes a lead screw with a diameter of 40.0mm, a pitch of 10.0mm, and a steel ball diameter of 6.35mm as an example. The metal ceramic powder is clad onto the surface of a bright metal steel rod substrate by laser cladding, and then subjected to deep cryogenic treatment. The material of the steel rod used is 42CrMo, and its heat treatment process is a quenching and tempering process (830-850℃×2.5h, then quenched with oil, then kept at 560-580℃ for 4h, then furnace cooled to 350 degrees Celsius and air cooled out of the furnace). The diameter of the steel rod is 31mm, the thickness of the metal ceramic layer is 5mm, the outer diameter of the lead screw after cladding is 41.0mm, and the final outer diameter size is 40mm after a series of grinding processes. In terms of mass percentage, the metal ceramic powder used is composed of 25% WC, 15% TiC, 10% SiC and 50% 42CrMo; the hardness of the cladding layer is 63-65HRC.
[0066] The process parameters of laser cladding are: laser power 2000W, powder feeding amount 18g / min, spot size 4mm, moving line speed 15mm / s, overlap rate 40%, and inert gas flow rate 15L / min.
[0067] The cryogenic treatment process is as follows: cooling rate 5°C / min, holding temperature -80°C, holding time 2 hours, heating rate 5°C / min to room temperature.
[0068] The specific laser cladding steps are as follows:
[0069] First, a 1.2mm thick metal ceramic layer is clad on the surface of the steel rod; the second layer is clad along the spiral line, with a width of 0.9 times the pitch, i.e. 9.0mm, and a thickness of 0.8mm; the third layer is clad along the above spiral line, with a width of 0.7 times the pitch, i.e. 7.0mm, and a thickness of 1.0mm; the fourth layer is clad along the above spiral line, with a width of 0.5 times the pitch, i.e. 5.0mm, and a thickness of 1.0mm; the fifth layer is clad along the above spiral line, with a width of 0.4 times the pitch, i.e. 4.0mm, and a thickness of 1.0mm.
[0070] Example 2
[0071] This embodiment takes a lead screw with a diameter of 63.0mm, a pitch of 16.0mm, and a steel ball diameter of 10.0mm as an example, and uses laser cladding to clad the metal ceramic powder onto the surface of the iron-based bright steel rod substrate, and then performs deep cryogenic treatment on it. The material of the steel rod used is GCr15, and its heat treatment process is a spheroidizing annealing process (isothermal spheroidizing annealing process: 770-790℃×2h, furnace cooling to 690-710℃×3h, furnace cooling to below 500℃ and air cooling). The diameter of the steel rod is 50.0mm, the thickness of the ceramic layer is 7.0mm, the outer diameter after cladding is 64.0mm, and the final outer diameter size after a series of grinding processes is 63.0mm. In terms of mass percentage, the composition of the metal ceramic powder used is 25% WC, 20% TiC, 15% SiC and 40% GCr15; the hardness of the cladding layer is 63-65HRC.
[0072] The process parameters of laser cladding are: laser power 2300W, powder feeding amount 25g / min, spot size 5mm, moving line speed 18mm / s, overlap rate 50%, and inert gas flow rate 18L / min.
[0073] The cryogenic treatment process is as follows: cooling rate 6°C / min, holding temperature -100°C, holding time 3 hours, heating rate 6°C / min to room temperature.
[0074] The specific laser cladding steps are as follows:
[0075] First, a 1.5mm thick metal ceramic layer is clad on the surface of the steel rod; the second layer is clad along the spiral line, with a width of 0.9 times the pitch, i.e. 14.4mm, and a thickness of 1.0mm; the third layer is clad along the above spiral line, with a width of 0.7 times the pitch, i.e. 11.2mm, and a thickness of 1.0mm; the fourth layer is clad along the above spiral line, with a width of 0.55 times the pitch, i.e. 8.8mm, and a thickness of 1.5mm; the fifth layer is clad along the above spiral line, with a width of 0.45 times the pitch, i.e. 7.2mm, and a thickness of 2.0mm.
[0076] Example 3
[0077] This embodiment takes a lead screw with a diameter of 80mm, a pitch of 40mm, and a steel ball diameter of 12.7mm as an example. The metal ceramic powder is clad onto the surface of an iron-based bright steel rod by laser cladding, and then subjected to deep cryogenic treatment. The material of the steel rod used is 40Cr, and its heat treatment process is a quenching and tempering process (830-850℃×2h, oil quenching, then 600-620℃ insulation for 4h, furnace cooling to 350℃, and air cooling after exiting the furnace). The diameter of the rod used is 64mm, the thickness of the metal ceramic layer is 8.5mm, the outer diameter after cladding is 81.0mm, and the final outer diameter size after a series of grinding processes is 80.0mm. In terms of mass percentage, the metal ceramic powder composition is 30% WC, 20% TiC, 20% SiC and 30% 40Cr; the hardness of the cladding layer is 63-65HRC.
[0078] The process parameters of laser cladding are: laser power 2500W, powder feeding amount 30g / min, spot size 5mm, moving line speed 20mm / s, overlap rate 60%, and inert gas flow rate 25L / min.
[0079] The cryogenic treatment process is as follows: cooling rate 8°C / min, holding temperature -120°C, holding time 4 hours, heating rate 10°C / min to room temperature.
[0080] The specific laser cladding steps are as follows:
[0081] First, a 1.5mm thick metal ceramic layer is clad on the surface of the steel rod; the second layer is clad along the spiral line, with a width of 0.95 times the pitch, i.e. 38.0mm, and a thickness of 1.0mm; the third layer is clad along the above spiral line, with a width of 0.85 times the pitch, i.e. 34.0mm, and a thickness of 1.5mm; the fourth layer is clad along the above spiral line, with a width of 0.76 times the pitch, i.e. 30.4mm, and a thickness of 1.5mm; the fifth layer is clad along the above spiral line, with a width of 0.72 times the pitch, i.e. 28.8mm, and a thickness of 3.0mm.
[0082] Comparative Example 1
[0083] In Comparative Example 1, no metal ceramic layer was clad on the surface of the steel rod substrate. A steel rod with the same material as that of Example 1 was directly used with a diameter of 41 mm. It was processed into a finished product through the traditional method of "induction quenching-straightening-whirlwind milling-straightening-precision grinding", wherein the induction quenching process was as follows: a 200kW, 10kHz induction quenching machine was used, a workpiece moving speed of 0.5m / min, and a workpiece temperature of 860-880°C.
[0084] Comparative Example 2
[0085] Comparative Example 2 is similar to Example 1, except that: the number of laser cladding layers is changed to 7 layers, the first cladding thickness is 1.2 mm; the second cladding thickness is 0.5 mm, and the width is 9.5 mm; the third cladding thickness is 0.5 mm, and the width is 9.0 mm; the fourth cladding thickness is 0.5 mm, and the width is 7.5 mm; the fifth cladding thickness is 0.5 mm, and the width is 7.0 mm; the sixth cladding thickness is 0.8 mm, and the width is 5.5 mm; the seventh cladding thickness is 1.0 mm, and the width is 4.0 mm; the laser power is 4100 W, the powder feeding amount is 10 g / min, the moving linear speed is 30 mm / s, the overlap rate is 80%, and the inert gas flow rate is 18 L / min; the other conditions are the same as Example 1.
[0086] In this comparative example, because the thickness of the single-layer cladding layer became thinner, in order to ensure the cladding effect, the laser cladding parameters were adjusted. If they were not adjusted, there would be a risk of failure to clad or serious damage to the substrate.
[0087] Comparative Example 3
[0088] Comparative Example 3 is similar to Example 3, except that the number of laser cladding layers is changed to 3 layers, the first layer has a cladding thickness of 2.0 mm, the second layer has a cladding thickness of 3.0 mm, and a width of 37.0 mm; the third layer has a cladding thickness of 3.5 mm and a width of 34 mm; the moving linear speed of the laser cladding process is 15 mm / s, and the overlap rate is 40%; the other conditions are the same as Example 3.
[0089] Comparative Example 4
[0090] Comparative Example 4 is similar to Example 1, except that: a rod with a diameter of 35 mm is selected, and the cladding thickness is 0.07 times the diameter, i.e. 2.8 mm; first, a metal ceramic layer with a thickness of 1.2 mm is clad on the surface of the metal rod; the second layer has a width of 9.0 mm and a thickness of 0.4 mm; the third layer has a width of 0.7 times the pitch, i.e. 7.0 mm, and a thickness of 0.4 mm; the fourth layer has a width of 0.5 times the pitch, i.e. 5.0 mm, and a thickness of 0.4 mm; the fifth layer has a width of 0.4 times the pitch, i.e. 4.0 mm, and a thickness of 0.4 mm; the laser power is 3800 W, the powder feeding amount is 12 g / min, the moving linear speed is 35 mm / s, the overlap rate is 85%, and the inert gas flow rate is 20 L / min; the other conditions are the same as Example 1.
[0091] Comparative Example 5
[0092] Comparative Example 5 is similar to Example 1, with the following differences: a rod with a diameter of 28 mm is selected, and the cladding thickness is 0.16 times the diameter, i.e. 6.4 mm; first, a metal ceramic layer with a thickness of 2 mm is clad on the surface of the metal rod; the second layer has a width of 9.0 mm and a thickness of 1.0 mm; the third layer has a width of 0.7 times the pitch, i.e. 7.0 mm, and a thickness of 1.0 mm; the fourth layer is clad along the spiral line, with a width of 0.5 times the pitch, i.e. 5.0 mm, and a thickness of 1.0 mm; the fifth layer is clad along the spiral line, with a width of 0.4 times the pitch, i.e. 4.0 mm, and a thickness of 1.4 mm; the remaining conditions are consistent with Example 1.
[0093] Comparative Example 6
[0094] Comparative Example 6 is similar to Example 2, except that the insulation temperature of the cryogenic treatment process is changed to -60°C, and the other conditions are the same as those of Example 2.
[0095] Comparative Example 7
[0096] Comparative Example 7 is similar to Example 2, except that the insulation temperature of the cryogenic treatment process is changed to -140°C, and the other conditions are the same as those of Example 2.
[0097] Comparative Example 8
[0098] Comparative Example 8 is similar to Example 1, with the only difference being that the iron-based powder 42CrMo is replaced with an equal amount of 40Cr, and the other conditions are the same as those of Example 1.
[0099] Test example
[0100] The deformation increase, wear, accuracy retention and mean time between failures (MTBF) of the lead screw obtained in each embodiment and each comparative example were tested. The test method referred to the method in the industry standard JB / T 13813.2-2020, and the test results are shown in Table 1.
[0101] Table 1
[0102] Deformation increase Wear Precision retention MTBF Example 1 0.08mm / m 0.8mg 6015h 15236h Example 2 0.06mm / m 0.6mg 6225h 16123h Example 3 0.05mm / m 0.5mg 6486h 16585h Comparative Example 1 0.8mm / m 2.5mg 4002h 10423h Comparative Example 2 0.2mm / m 1.5mg 4200h 8500h Comparative Example 3 0.08mm / m 1.2mg 3000h 6000h Comparative Example 4 0.08mm / m 5.3mg 2000h 4000h Comparative Example 5 0.2mm / m 1.0mg 3500h 7000h Comparative Example 6 0.1mm / m 1.2mg 4525h 8983h Comparative Example 7 0.08mm / m 0.8mg 5432h 12581h Comparative Example 8 0.08mm / m 1.0mg 3800h 7500h
[0103] It can be seen from the data in Table 1 that the screw prepared by the method of the present invention has a small increase in deformation, a small amount of wear, good wear resistance, a long precision retention time and a mean time between failures, good precision retention, and a long service life; compared with the traditional processing method in Comparative Example 1, the wear amount is significantly reduced, and the precision retention and the mean time between failures are significantly improved; from the comparison between Comparative Example 2 and Example 1, it can be seen that too many layers of laser cladding layers will lead to a decrease in the bonding force of the cladding layer, and a significant decrease in wear resistance, precision retention, and MTBF; from the comparison between Comparative Example 3 and Example 3, it can be seen that too few layers of laser cladding layers and too large a single layer thickness will reduce the toughness of the cladding layer, increase the brittleness, and reduce the wear resistance and precision. The degree retention and MTBF are significantly reduced; from the comparison of Comparative Example 4, Comparative Example 5 and Example 1, it can be seen that too large or too small total thickness of the metal ceramic layer will lead to decreased wear resistance and precision retention; from the comparison of Comparative Example 6 and Comparative Example 7 with Example 2, it can be seen that the cryogenic treatment temperature has a great influence on the wear resistance and precision retention of the screw, and too high or too low cryogenic treatment temperature will lead to decreased wear resistance and precision retention of the screw; from the comparison of Comparative Example 8 and Example 1, it can be seen that adding iron-based powder with the same composition as the steel rod substrate to the metal ceramic powder can improve the bonding force between the metal ceramic layer and the steel rod substrate, thereby improving the wear resistance and precision retention of the screw.
[0104] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A lead screw, characterized in that: The invention comprises a cylindrical steel rod substrate and a metal ceramic layer located on the outer surface of the steel rod substrate. The metal ceramic layer is a multilayer structure, comprising a ceramic base layer covering the entire circumferential outer surface of the steel rod substrate and a threaded layer located on the ceramic base layer.
2. The lead screw according to claim 1, characterized in that The thickness H of the metal ceramic layer and the diameter D of the lead screw satisfy the following relationship: H=(0.08-0.15)D.
3. The lead screw according to claim 1, characterized in that In terms of mass percentage, the metal ceramic layer includes 10% to 60% WC, 0% to 40% TiC, 0% to 40% SiC, and 20% to 60% iron-based material having the same composition as the steel rod substrate; And / or, the steel rod substrate includes any one of 42CrMo steel, GCr15 steel, and 40Cr steel.
4. The lead screw according to claim 1, characterized in that The number of layers n of the metal ceramic layer is 4 to 6, wherein the first layer is the ceramic base layer, the second to nth layers constitute the threaded layers, and the thread width of the threaded layers decreases layer by layer starting from the second layer.
5. The lead screw according to claim 1, characterized in that In the multilayer structure of the metal ceramic layer, the thread width of the second layer is 0.85 to 0.95 times the pitch of the lead screw; and / or the thickness of any layer is 0.01 to 0.04 times the diameter of the lead screw.
6. The method for preparing a lead screw according to any one of claims 1 to 5, characterized in that: The following steps are involved: The steel rod substrate is heat treated, and metal ceramic powder is clad on the outer peripheral surface of the steel rod substrate in multiple layers by laser cladding to form a metal ceramic layer, which is then cryogenically treated and ground to obtain a metal ceramic layer; The cladding step includes cladding a cladding layer on the entire outer circumference of the steel rod substrate to form a ceramic base layer, then cladding along a spiral line on the ceramic base layer to obtain a spiral second cladding layer, and continuing to clad along the spiral line on the second cladding layer, and repeating this process until a thread layer of desired thickness is obtained.
7. The method for preparing a lead screw according to claim 6, characterized in that: Calculated by mass percentage, the metal ceramic powder includes 10% to 60% of WC, 0% to 40% of TiC, 0% to 40% of SiC, and 20% to 60% of iron-based powder having the same composition as the steel rod substrate.
8. The method for preparing a lead screw according to claim 6, characterized in that: Contains at least one of the following characteristics: (1) The laser power of the laser cladding is 1000 to 5000 W; (2) The powder feeding rate of the laser cladding is 10 to 50 g / min; (3) The spot size of the laser cladding is 2 to 6 mm; (4) The moving linear speed of the laser cladding is 5 to 50 mm / s, and the overlap rate is 5% to 80%; (5) Inert gas is used to protect the cladding parts during the cladding process, and the flow rate of the inert gas is 10 to 50 L / min; (6) The number of layers of the laser cladding is 4-6 layers.
9. The method for preparing a lead screw according to claim 6, characterized in that: The temperature of the deep freezing treatment is -80°C to -120°C, and the time of the deep freezing treatment is 1 to 5 hours.
10. A ball screw pair, characterized in that: A lead screw comprising any one of claims 1 to 5, or a lead screw produced by the method for producing a lead screw as described in any one of claims 6 to 9.
Citation Information
Patent Citations
Method for strengthening extruder screw by using laser
CN104611695A
Laser cladding repair method for local damage of external threads of aircraft undercarriage axle
CN112663051A
Iron-based laser cladding material and wear-resistant iron-based laser cladding layer
CN115673314A
Metal ceramic screw
CN209616276U
Laser cladding alloy screw
CN209616305U